Evaluating the Comprehensive Benefit of Public Transport Service – The Perspective of Three Stakeholders - Zhang, Chunqin; Hu, Yuting; Lu, Weite (Promet - Traffic&Transportation, 2022)
Most studies investigate the benefit of public trans-port service from either the perspective of the operators or the public individually, failing to bind them together. Furthermore, they have not considered the significance of the government in quantifying the benefit. This pa-per explores the comprehensive benefit of public trans-port service from the perspectives of three stakeholders; namely, the operators, the public, and government. We develop a comprehensive benefit evaluation tool that is able to quantify production efficiency, service effect, and environmental effect, and test the effectiveness of the tool through a case study in 36 central cities of China. A network data envelopment analysis (NDEA) is used to evaluate the efficiency of the production and service sub-process, and comprehensive benefits. The results re-veal the following: (1) during the period 2010–2017, the production efficiency in 36 central cities showed a down-ward trend; (2) the service effectiveness did not change considerably from 2010 to 2013 but declined gradual-ly during the period 2014–2017; (3) the comprehensive benefits rarely changed during the period 2010–2013, but gradually got worse in response to reductions in the production efficiency and service effectiveness during the period 2014–2017. This study offers a robust tool to mea-sure the benefits of public transport in China for better decision-making, in terms of transit operation and man-agement.